Deinstitutionalised patients, homelessness and imprisonment: systematic review - Winkler, Petr; Barrett, Barbara; McCrone, Paul; Csémy, Ladislav; Janoušková, Miroslava; Höschl, Cyril (British journal of psychiatry, 2016)
BACKGROUND: Reports linking the deinstitutionalisation of psychiatric care with homelessness and imprisonment have been published widely. AIMS: To identify cohort studies that followed up or traced back long-term psychiatric hospital residents who had been discharged as a consequence of deinstitutionalisation. METHOD: A broad search strategy was used and 9435 titles and abstracts were screened, 416 full articles reviewed and 171 articles from cohort studies of deinstitutionalised patients were examined in detail. RESULTS: Twenty-three studies of unique populations assessed homelessness and imprisonment among patients discharged from long-term care. Homelessness and imprisonment occurred sporadically; in the majority of studies no single case of homelessness or imprisonment was reported. CONCLUSIONS: Our results contradict the findings of ecological studies which indicated a strong correlation between the decreasing number of psychiatric beds and an increasing number of people with mental health problems who were homeless or in prison.
Keywords: deinstitucionalizace; duševně nemocní; Persons with Psychiatric Disorders; vězni; Prisoners; Humans; lidé; Deinstitutionalization; Ill-Housed Persons; lidé bez domova